Comparison of Quinn's Advantage fertilization medium and tissue culture medium 199 for in vitro maturation of oocytes - Yu-Hung Lin; Jiann-Loung Hwang; Lee-Wen Huang; Kok-Min Seow; Bih-Chwen Hsieh; Chii-Ruey Tzeng (Elsevier, 2014)
Objective: The purpose of the study was to compare the Quinn's Advantage fertilization medium (Q1) and the tissue culture medium 199 (TCM199) for in vitro maturation (IVM) of oocytes and ammonium production during IVM. Materials and methods: The immature murine oocytes were randomly added into Q1 and TCM199. Ammonium concentrations were measured at the start and after 18 hours of IVM, and the mature oocytes were fertilized and cultured into blastocysts. The blastocysts were then stained for inner cell mass (ICM) and trophectoderm. Results: The maturation rate was higher in Q1 than in TCM199 (85.7% vs. 76.6%, p = 0.024). The fertilization and blastocyst rates were slightly higher in Q1, but not significant. Differential staining of the blastocysts showed slightly higher ICM ratio in the blastocysts derived from Q1. Mean ammonium concentrations in Q1 and TCM199 at Time 0 were 184.9 and 339.2 μg/dL, respectively (p = 0.05), and after 18 hours of IVM were 268.7 and 443.6 μg/dL, respectively (p = 0.045). Addition of ammonium chloride into Q1 adversely affects IVM. Conclusion: Q1 is superior to TCM199 in terms of oocyte maturation, which may be due to lower ammonium concentration.